Analysis and Synthesis of Positive Systems Under ℓ1 and L1 Performance - Chen, Xiaoming; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This thesis introduces novel and significant results regarding the analysis and synthesis of positive systems, especially under l1 and L1 performance. It describes stability analysis, controller synthesis, and bounding positivity-preserving observer and filtering design for a variety of both discrete and continuous positive systems. It subsequently derives computationally efficient solutions based on linear programming in terms of matrix inequalities, as well as a number of analytical solutions obtained for special cases. The thesis applies a range of novel approaches and fundamental techniques to the further study of positive systems, thus contributing significantly to the theory of positive systems, a "hot topic" in the field of control. .
Introduction -- ℓ1-induced Controller Design for Positive Systems -- L1-induced Output-Feedback Controller Synthesis for Interval Positive Systems -- Positive State-Bounding Observer for Interval Positive Systems -- Positive Filtering for Positive Systems under L1 Performance -- Controller and Filter Syntheses for Positive Takagi-Sugeno Fuzzy Systems under ℓ1 Performance -- Conclusions and Future Work.
Keywords: Control engineering; Mechanical engineering; Microprogramming .; Control and Systems Theory; Mechanical Engineering; Control Structures and Microprogramming